2010
DOI: 10.3892/ijo_00000683
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac alterations in cancer-induced cachexia in mice

Abstract: Abstract. Cachexia is a common syndrome in advanced cancer patients and causes up to 22% of cancer-related deaths. It remains elusive whether cancer cachexia causes heart failure. We investigated the effect of cancer cachexia on heart function and cardiac muscle structure in a mouse model. Male CD2F1 mice were inoculated with either colon-26 adenocarcinoma cells (Tumor group) or vehicle (PBS) (No Tumor group and Pair-fed group). Heart function as measured by fractional shortening in vivo using transthoracic ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
21
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 38 publications
5
21
1
4
Order By: Relevance
“…Notably, cardiac contractile function was maintained in the SS-31-treated C26 mice independent of preservation of cardiac mass. While the mechanisms are unclear, this observation is consistent with findings by Tian et al which revealed a significant reduction in absolute cardiac mass in C26 tumor-bearing mice and pair-fed mice compared to non-tumor-bearing mice; however, fractional shortening was maintained in pair-fed mice compared to C26 tumor-bearing mice [30].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Notably, cardiac contractile function was maintained in the SS-31-treated C26 mice independent of preservation of cardiac mass. While the mechanisms are unclear, this observation is consistent with findings by Tian et al which revealed a significant reduction in absolute cardiac mass in C26 tumor-bearing mice and pair-fed mice compared to non-tumor-bearing mice; however, fractional shortening was maintained in pair-fed mice compared to C26 tumor-bearing mice [30].…”
Section: Discussionsupporting
confidence: 91%
“…Muscle mass was also preserved in C26 mice treated with SS-31. While changes in food intake could contribute to our findings, pair-fed and cachectic C26 tumor-bearing mice showed significant differences in cardiorespiratory muscle function and muscle mass when compared [29,30]. These data suggest that the effects to diaphragm and cardiac muscle were the result of tumor growth and SS-31 treatment.…”
Section: Discussionmentioning
confidence: 64%
“…In the present study, mice did not show signs of systemic inflammation, as the circulating levels of CRP and TWEAK were not increased, and this was paralleled by the absence of muscle wasting. Thus, our data suggest that tumor burden per se induces cardiac remodeling that precedes muscle wasting, which might be exacerbated when cachexia is established, as previously reported [20,21]. This cardiac remodeling observed in tumor-bearing mice was characterized by alterations on mitochondrial proteome with emphasis on the up-regulation of the biological process “cardiac tissue morphogenesis” and the down-regulation of “cellular respiration”.…”
Section: Discussionsupporting
confidence: 82%
“…Tumor-bearing mice also exhibited increased cardiac fibrosis, decreased cardiac myofibrillar proteins, increased protein ubiquitination, and altered composition of MHC. Increased expression of brain natriuretic peptide, c-Fos and decreased peroxisome proliferator-activated receptor α and its responsive gene carnitine palmitoyltransferase 1 are noted in tumor-bearing mice[17, 18]. The expression of biomarkers of protein degradation is increased in the hearts of female CD2F1 mice with systolic and diastolic dysfunction induced by colon-26 tumor cells[19].…”
Section: Introductionmentioning
confidence: 99%
“…The expression of biomarkers of protein degradation is increased in the hearts of female CD2F1 mice with systolic and diastolic dysfunction induced by colon-26 tumor cells[19]. Others have found heart failure, decreased cardiac cell size, increased autophagy and normal caspase 3 activity and protein ubiquitination in male (but not female) CD2F1 (Balb/c X DBA2) mice injected with colon-26 adenocarcinoma cells[18, 20, 21]. In sum, animal models demonstrate reduced cardiac function, increased cardiac fibrosis with variable evidence for altered protein ubiquitination.…”
Section: Introductionmentioning
confidence: 99%